2020
DOI: 10.1038/s41598-020-64589-x
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution in situ analysis of active ribosomal DNA chromatin organization in the nucleolus

Abstract: Ribosomal RNA (rRNA) transcription by RNA polymerase I (Pol I) is the first key step of ribosome biogenesis. While the molecular mechanisms of rRnA transcription regulation have been elucidated in great detail, the functional organization of the multicopy rRnA gene clusters (rDnA) in the nucleolus is less well understood. Here we apply super-resolution 3D structured illumination microscopy (3D-SiM) to investigate the spatial organization of transcriptionally competent active rDnA chromatin at size scales well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…2f ), apparently the GC. This strong colocalization was nicely supported by the Pearson’s correlation coefficients (PCC) 46 between the distributions of the two factors in multiple cells (Supplementary information, Fig. S 13c ).…”
Section: Resultssupporting
confidence: 52%
“…2f ), apparently the GC. This strong colocalization was nicely supported by the Pearson’s correlation coefficients (PCC) 46 between the distributions of the two factors in multiple cells (Supplementary information, Fig. S 13c ).…”
Section: Resultssupporting
confidence: 52%
“…New avenues of spatial multi-omics are just now being explored and could have a great impact on the construction of atlases with many maps. Furthermore, these technologies open up new avenues to study gene perturbations (Wang et al, 2019), cell lineage tracing (Chen et al, 2018;Frieda et al, 2017), and other aspects of functional DNA and RNA biology (Cai et al, 2020;Maiser et al, 2020).…”
Section: Integrative In Situ Measurementsmentioning
confidence: 99%
“…A number of factors, including TTF-1 and c-Myc, have also been identified as being involved in this loop formation. Direct evidence of active rDNA looping was recently presented by Maiser and colleagues [ 81 ]. Ray et al showed that, in human cells, Top IIα altered the rDNA topology at the rRNA core promoter and this was required for the assembly of functional PICs [ 58 ].…”
Section: Regulation Of Ribosomal Gene Transcriptionmentioning
confidence: 99%